Bodies in Times of War: A Comparison of Hijikata Tatsumi and Mary Wigman's Use of Dance as Political Statement. (2014) - Calamoneri, Tanya
Abstract : How does the representation of bodies change in times of war? How can dance be political activism? This paper considers the dances of Hijikata Tatsumi and Mary Wigman in relation to their experiences of war, and explores their use/representation of the body as a political statement. In both cases, these artists sought to use dance to rescue the body from its subjugated social standing. Mary Wigman's dance technique is influenced by German korperkultur, and had its birth in her work with Rudolph Laban and at the natural paradise of Hellerau. Wigman admired Nietzsche's desire to rescue the body from "despisers of the body, " who saw the physical body as an obstacle that must be denied in order for the soul to reach salvation. For Wigman, the "sensuous dancing body" that Nietzsche referred to in Zarathustra "became the vehicle to an authentic life." Hijikata's idea of dancers as "lethal weapons that dream" offered a view of bodies that were aware of personal agency and chose to step outside of usefulness for the elusive "advancement" of society. He explains, "in this sense my dance, based on human self-activation … can naturally be a protest against the 'alienation of labor' in capitalist society." Douglass Slaymaker's writing on post-war Japanese literature frames Hijikata's sentiment in the time: images of body as nikutai [flesh] were considered counterhegemonic because they defied the notion that the individual body belonged to the national body. Hijikata redirected the body's sacrifice away from productivity and toward the creation of art.